Eventos interativos em sala de aula: estratégias discursivas do professor - Oliveira, M. Bernadete F. de (Cadernos de Linguagem e Sociedade, 2010)
The reflection presented in this paper intends to contribute to the discussion on the role of language in the knowledge acquisition process. The paper analyses verbal strategies teachers use in the classroom, in different interactional situations, based on Bakhtin’s concept of dialogism and on Vygotsky’s semiotic mediational process.